The Effect of Time Pressure and Supervision Actions on Premature Termination of Audit Procedures at the Syamsul Bahri TRB Public Accounting Firm - Muammar Rinaldi; Indra Mawanta Ginting; Irawan, Dedi (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
This study aims to determine whether Time Pressure has a significant effect on Premature Sign off of Audit Procedures at Syamsul Bahri TRB Public Accounting Firm, knowing whether Supervision have a significant effect on Premature Sign off of Audit Procedures at Syamsul Bahri TRB Public Accounting Firm and find out whether time pressure and supervision has a significant effect on premature sign off of audit procedures at Syamsul Bahri TRB Public Accounting Firm. The research methodology used is descriptive quantitative method. The type of data used in this study is quantitative data, namely data obtained in the form of numbers or numbers. Data sources are primary and secondary data. Primary data is obtained from questionnaires while secondary data is obtained from theories and journals related to the variables under study. The population in this study was the auditor of Syamsul Bahri's Accounting Office, which amounted to 37 auditors. By using census samples, the number of samples obtained is 37 auditors. The results of the analysis showed that Time Pressure had a significant effect on Premature Sign off of the audit procedures at Syamsul Bahri TRB Public Accounting Firm based on the results of partial hypothesis testing, namely tcount (5,854) <t table (2,03224). The results of the analysis show that Supervision have a significant effect on Premature Sign off of the Audit Procedures at the Syamsul Bahri TRB Public Accounting Firm based on the results of the partial hypothesis test, namely tcount (3.773)> t table (2.03224). The results showed that time pressure and supervision had a significant effect on Premature Sign off of the audit procedures at Syamsul Bahri TRB Public Accounting Firm based on the results of simultaneous hypothesis testing, which was equal to Fcount (25,569)> (Ftable) = (3,28). The results of this study are supported by the value of R square (R2) = 0.601 or 60.1% which means that Time Pressure and Supervision simultaneously have an effect of 39.9% on Premature Sign off of Audit Procedures. While the remaining 59.1% is influenced by other variables not examined, such as materiality, Locus of Control, Risk Audit, Review Procedure, ethical awareness and others.